Developing a Genetic Fuzzy System Model for Cost-Benefit Analysis. - Singh, Saurabh; Shukla, Praveen Kumar; Ranjan, Rashmi; Kumar, Anurag (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Cost benefit analysis is a systematic approach for calculation and analyzing the cost of a project. Soft computing approaches are also applicable to deal with cost benefit analysis. In this paper Mamdani fuzzy system has been developed for cost benefit analysis. The genetic optimization of the model is carried out. The interpretability and accuracy features are also analyzed.